2019
DOI: 10.1371/journal.pone.0225805
|View full text |Cite|
|
Sign up to set email alerts
|

Food from faeces: Evaluating the efficacy of scat DNA metabarcoding in dietary analyses

Abstract: Scat DNA metabarcoding is increasingly being used to track the feeding ecology of elusive wildlife species. This approach has greatly increased the resolution and detection success of prey items contained in scats when compared with other classical methods. However, there have been few studies that have systematically tested the applicability and reliability of this approach to study the diet of large felids species in the wild. Here we assessed the effectiveness of this approach in the cheetah Acinonyx jubatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…It should be noted that DNA metabarcoding have some limitations when is used in diet-related studies, such as DNA degradation from the time of feeding until the sample collection, DNA extraction efficiency, selection of molecular markers, PCR inhibition or uncompleted reference databases 72 74 . In addition, DNA metabarcoding without microscope analysis does not determine the trophic position of each detected prey species in the food web.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that DNA metabarcoding have some limitations when is used in diet-related studies, such as DNA degradation from the time of feeding until the sample collection, DNA extraction efficiency, selection of molecular markers, PCR inhibition or uncompleted reference databases 72 74 . In addition, DNA metabarcoding without microscope analysis does not determine the trophic position of each detected prey species in the food web.…”
Section: Discussionmentioning
confidence: 99%
“…While this aspect has to be accounted for when interpreting eDNA metabarcoding results for diet assessments, it has useful implications in the context of biodiversity surveys. However, taxa detectability varies in metabarcoding approaches as well, due to a number of widely acknowledged biological and technical reasons 45 , 62 that should be considered when designing a study and drawing inferences.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, we used the function prop.test , which is a 2-sample test for equality of the proportion of sequences identified to each taxonomic level (order, family, genus and species) between the two sample age categories. The two age categories are meant to serve as a broad separation between relatively “fresh” and “older” samples that are likely to be significantly affected by DNA degradation as a result of the cumulative effect of multiple factors acting during sample exposure to the environment (see also 36 , 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Validation studies using mock communities or captive animals fed a known diet, have been conducted for a wide range of consumers and prey and have shown that although broad correlations are likely, especially at level of the presence/absence of prey taxa, biases may occur that need to be accounted for (reviewed in Deagle et al (2019), see also (Thuo et al, 2019). Therefore Deagle et al (2019) recommended to incorporate cross-validation in a study setup whenever possible.…”
Section: How Important Is Validation?mentioning
confidence: 99%